Analysis of disease burden in socially disadvantaged areas: Mapping of geographical inequalities in COVID-19 morbidity and mortality using a social disadvantage index in Tennessee - Antipova, Anzhelika (Frontiers in Sustainable Cities, 2022)
Social vulnerability is directly addressed by contemporaneous health research to improve social equity. Existing disadvantage indices capture vulnerability to COVID-19 pandemic less accurately. Health-related studies apply the indices to relate overall vulnerability to health outcomes including severe COVID-related health outcomes leading to hospitalization and death. The multi-variable indices are based on various attributes, some unrelated to COVID-19 severity. Some studies that use multi-attribute indices don't find meaningful association with COVID-19 health outcomes. Additionally, current research is lacking on health impacts of social disadvantage during various COVID-19 stages. Thus, due to variations in inequality in exposure and pandemic susceptibility, community health should be assessed at different time points. To fill this gap, we develop an index using six indicators capturing pandemic vulnerability. We apply it in a retrospective case study of a relationship between social disadvantage and morbidity and mortality due to COVID-19 focusing on disadvantaged communities set in Tennessee with a concentration of vulnerability and rurality. COVID-19-related health outcomes were tested for associations with a social disadvantage index (SDI) for earlier (2021) and later (2022) pandemic stages. First, we describe a methodology to create a social disadvantage index to identify communities at risk for severe COVID-19-related health outcomes based on the CDC guidance. Second, we highlight the differences in COVID-19 health outcomes over time as we examine health disparities associated with social disadvantage during various pandemic stages. To understand how the findings would differ if the same analyses were to be carried out using other vulnerability indices, we apply analyses to areas based on the CDC’s-based Social Vulnerability Index and find strong statistical association between the two indices and substantial overlap regarding disadvantaged areas identified and similar health outcome findings. A better understanding of whether residents of socially disadvantaged areas experience worse COVID-related health outcomes can help determine whether policies need to target not only individuals but entire communities to improve outcomes (Unger et al, 2021). The developed index based on six indicators is thus especially suitable during the COVID-19 disaster to efficiently identify vulnerable communities and address social equity.